530 FACTORS AFFECTING LONG-TERM MORTALITY AFTER ENDOVASCULAR REPAIR OF ABDOMINAL AORTIC ANEURYSMS. (1st January 2006) - de Virgilio, C.; Tran, J. K.; Donayre, C.; Lewis, R.; Dauphine, C.; Bui, H.; Walot, I.; Lippmann, M.; White, R.
Abstract : Background: Endovascular repair of abdominal aortic aneurysms (AAAs) has made considerable advancements with respect to perioperative mortality. However, fewer data are available regarding whether perioperative factors affect long-term mortality. Methods: We reviewed a prospective database of 468 patients from 1996-2004 who underwent endovascular infrarenal AAA repair. We analyzed preoperative, intraoperative, and immediate postoperative factors, using multivariate Cox proportional hazards models, to identify independent predictors of long-term survival (survival for at least 30 days after hospital discharge). Results: The mean age for our study population was 74 years and 90% were male. Median follow-up was 938 days (IQR 335-1479). Median overall survival was 2, 203 days (IQR 1093-2792). The leading cause of death was cardiac. On multivariate analysis, the number of preoperative clinical cardiac risk factors ( p = .0001), spending 2 or more days in the intensive care unit ( p < .0001), and having an ST segment elevation myocardial infarction (STEMI) in the perioperative period (p < .0001) were predictors of long-term mortality, as was the absence of an endoleak (p = .0013). A perioperative non-STEMI was not predictive of mortality. On multivariate analysis, only the number of preoperative clinical cardiac risk factors (p = .0001), spending 2 or more days in the ICU (p = .0006), and having a STEMI were predictors of long-term mortality. Conclusions: The leading cause of long-term mortality following endovascular AAA repair is cardiac. Preoperative variables such as clinical cardiac risk factors are significant predictors of long-term mortality following endovascular AAA repair, as is prolonged ICU stay and having a perioperative STEMI, whereas a perioperative non-STEMI is not. These findings provide guidelines for which patients are at greatest risk for long-term cardiac death following endovascular AAA repair and suggest that monitoring perioperative cardiac enzymes is unnecessary.